Idiopathic gynaecomastia in twins: a case report - Kumar, S.V.; Kumari, K. Lakshmi; Babu, P.V.S.S. Vijaya; Latha, K. Asha; Kumari, P. Kusuma (International Journal of Research in Medical Sciences, 2017)
Gynaecomastia is a common pathological condition of breast seen in men. This is defined as benign enlargement of breast tissue in males. It was first described by Palus Aegineta (AD 635-690). Herewith we are presenting cases of 14 year old twins attending the surgical O.P.D with bilateral enlarged breasts and pain. A diagnosis of pubertal gynaecomastia was made with no evidence of malignancy by histopathological examinations and mammography. One boy with 5 x 6 cm of right breast and 2 x3 cm of left breast was treated by subcutaneous mastectomy. Other boy had only enlargement of nipple and areola. He was reassured and sent home without surgical intervention. A rare case of idiopathic gynaecomastia in pubertal twins is described here.